Perceived risk factors for weight gain, barriers, and facilitators related to weight loss experienced by perimenopausal women: focus group discussion and thematic analysis. Issue 2 (February 2022) - Chopra, Sakshi; Ranjan, Piyush; Malhotra, Anita; Verma, Aditi; Kumari, Archana; Sharma, K. Aparna; Sarkar, Siddharth; Vikram, Naval K.
Abstract: Objective: This study aims to understand middle-aged perimenopausal women's perspectives and beliefs regarding their body weight status, and evaluate the barriers, and facilitators associated weight loss. Methods: Five focus group discussions were conducted with perimenopausal women (aged 40-55 y) who were recruited through convenience and snowball sampling. Discussions were conducted to understand their experiences related to weight management during the perimenopausal period. The discussions were audio-recorded and transcribed and data analysis was done using Atlas.ti software to generate codes, subthemes, and themes from the discussions. Results: A total of 23 women with a mean age of 46.6 ± 5.6 years were recruited. Several themes of risk factors of weight gain emerged like difficulty in physical activity, unhealthy eating, overeating, and religious and cultural practices. Appearance and prevention of health-related issues emerged as motivators of initiating weight loss. Barriers faced during weight loss included themes like difficulty in managing diet and activity, stress, socialization, and lack of time. Facilitators of weight loss included intrinsic motivation, experiencing early results and confidence in self-regulation. Conclusion: Women during their perimenopausal phase of life encounter a range of barriers and challenges related to weight loss. An understanding of these barriers might be useful to consider while planning strategies to regulate their weight. Abstract : Supplemental Digital Content is available in the text